Pilot Randomized Controlled Trial to Evaluate the Impact of Bed Rest on Maternal and Fetal Outcomes in Women with Preterm Premature Rupture of the Membranes - Bigelow, Catherine A.; Factor, Stephanie H.; Miller, Meredith; Weintraub, Andrea; Stone, Joanne (American Journal of Perinatology, 2016)
Objectives Preterm premature rupture of the membranes (PPROM) is spontaneous rupture of membranes before 37 weeks' gestation before the onset of labor. The standard of care is inpatient management with antibiotics and monitoring. Bed rest has not been shown to be beneficial in the setting of PPROM and has adverse maternal effects. We conducted a pilot randomized clinical trial (RCT) to determine the feasibility of recruitment for an RCT of this nature and obtain estimates of the frequency of maternal and neonatal outcomes.Study Design Patients who were diagnosed with PPROM < 34 weeks gestational age were randomized to bed rest versus activity in a 1:1 ratio. Subjects in both groups wore pedometers and kept activity logs. Maternal demographic and obstetric data and neonatal outcomes were collected and compared between groups using chi-square and Fisher exact tests. Latency was evaluated with log-rank test and Kaplan–Meier analysis.Results In this study, 36 women were enrolled and randomized; 1 patient withdrew. Complete data were available for 21 subjects. In univariable analysis, women in the activity group had a nonsignificantly shorter latency time than the bed rest group (median 6.0 vs. 8.5 days). Neonatal outcomes were similar between groups. Using log-rank sum analysis, neonates born to mothers in the activity group were more likely to develop necrotizing enterocolitis (NEC) than in the control group (24 vs. 0%, p = 0.05); this difference was not significant after false discovery rate correction (p = 0.80).Conclusion This is the first randomized controlled study to evaluate bed rest versus normal activity in the setting of PPROM < 34 weeks. This study demonstrates a nonsignificant increase in latency to delivery on bed rest and possible increase in NEC in the activity group; the mechanism remains unclear. We would recommend a larger RCT to better clarify these findings.
Keywords: activity restriction; bed rest; latency; necrotizing enterocolitis; preterm premature rupture of membranes